Designing of Ligand-107 an Effective Variant of Antimalarial Drug Lumefantrine through Structure-Based Computer-Aided Drug Development Approach - Ravi, Dr. Lokesh (Asian Journal of Pharmaceutics (AJP), 2020)
Background: Lumefantrine is a well-known antimalarial drug that has proven to be effective even against the multidrug-resistant Plasmodium sp. Although it is very effective, the shelf life of the drug is very short and is highly hydrophobic, hence, the drug has to be administered along with fat. Lumefantrine is also known for its undesired side effects that are overlooked in case of untreatable (drug resistant) malarial infections. Methodology: In this study, structure-based computational drug development approach was performed on lumefantrine structure to improve the biological properties using OSIRIS property explorer software. A total of 25 ligand molecules were designed that exhibited better Absorption, Distribution, Metabolism, Excretion, Toxicity (ADMET) properties. Results: A total of 20 drug targets were chosen and docked with lumefantrine to identify its potential target. Lumefantrine demonstrated significant affinity toward falcipain-3 protein with a free binding energy of âˆ’10.92 Kcal/mol and inhibition constant of 9.94 nM, suggesting that falcipain-3 is the potential drug target of lumefantrine. Among the 25 designed ligands with improved ADMET properties, ligand-107 demonstrated 100-fold higher affinity toward falcipain-3 with a free binding energy of âˆ’14.26 Kcal/mol and inhibition constant of 35.11 pM. Based on this improved affinity to inhibit falcipain-3 and based on improved ADMET properties of ligand-107, it was concluded to be the most effective variant of lumefantrine in this study. Conclusion: The result of the study could be greatly useful to pharmaceutical industries to develop an efficient antimalarial drug.